2011
DOI: 10.5354/0719-5370.2011.18496
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibilidad de Remociones en Masa Costeras y Amenazas Asociadas en la Patagonia Chilena: El Caso del Área de Hornopirén (42ºS)

Abstract: Las remociones en masa costeras pueden ser una importante fuente de riesgo en ambientes de fiordos, con el potencial de causar daños directos a poblaciones locales, así como daños indirectos por la generación de tsunamis locales destructores. Distintos tipos de remoción en masa pueden ser desencadenados ya sea por lluvias intensas o actividad sísmica, como ocurrió en el fiordo Aysén en el sur de Chile durante el terremoto de 2007 en la Zona de Falla Liquiñe-Ofqui (LOFZ). En este trabajo se analiza el área de f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Landslide inventory: A photointerpretation of aerial photographs (1982, 1997, 1:20,000 and 1:70,000) and Google Earth was completed and validated by fieldwork. Landslides were identified by morphological evidence, according to the criteria of Náquira [45], Sepúlveda and Serey [30] and Sepúlveda et al [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] for fjord environments. Vegetated landslides were also identified that occurred in the past but at unknown dates.…”
Section: Methodsmentioning
confidence: 99%
“…Landslide inventory: A photointerpretation of aerial photographs (1982, 1997, 1:20,000 and 1:70,000) and Google Earth was completed and validated by fieldwork. Landslides were identified by morphological evidence, according to the criteria of Náquira [45], Sepúlveda and Serey [30] and Sepúlveda et al [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] for fjord environments. Vegetated landslides were also identified that occurred in the past but at unknown dates.…”
Section: Methodsmentioning
confidence: 99%